Nickel carbide dispersion strengthening enhanced copper-nickel-tin alloy and preparation method thereof
By uniformly dispersing nickel carbide (Ni3C) in copper-nickel-tin alloy and controlling the alloy structure, the problems of coarse grains and serious segregation in the alloy are solved, and the mechanical properties and corrosion resistance of the alloy are significantly improved.
Patent Information
- Application Number
- CN202411276803.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-02-07
AI Technical Summary
During the smelting and casting process, copper-nickel tin alloys are prone to coarse internal grains and severe inter-grain segregation, resulting in uneven composition and affecting the mechanical properties of the alloy and product quality.
By using nickel carbide as a diffusion reinforced phase, the nickel particles are combined with graphene atomic level through high-energy ball milling to generate Ni3C, which is uniformly dispersed in the copper-nickel-tin alloy, and the alloy structure size and morphology are regulated.
Refine grains, reduce intergranular segregation, improve the mechanical strength and corrosion resistance of the alloy, and improve the performance of the material at high temperatures.
Smart Images

Figure CN119392034A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of alloy materials, and in particular to a nickel carbide dispersion-strengthened copper-nickel-tin alloy and a preparation method thereof. Background Art
[0002] Copper-nickel-tin alloy has the advantages of high strength, high elastic modulus, high wear resistance and corrosion resistance, and is widely used in electronics, electricity, machinery, transportation, aerospace and other fields. In the smelting and casting process of copper-nickel-tin alloy, the transformation from liquid phase to solid phase is involved. Due to the high content of nickel and tin, the crystallization temperature range of the alloy is wide, which can easily cause coarse internal grains and serious intergranular segregation, resulting in uneven composition, which will affect the mechanical properties and product quality of the alloy. Although hot working deformation can regulate the size and morphology of the organization to improve the performance of the alloy, the improvement ability is limited. With the development of science and technology, various fields have put forward higher requirements for material properties. How to break through the traditional material composition design and subsequent processing deformation, heat treatment and other means to improve metal properties has become a bottleneck problem in the current research in the field of materials, and the introduction of composite materials with strengthening phases is one of the hot directions to solve this bottleneck problem.
[0003] By introducing a dispersion strengthening phase into the copper-nickel-tin alloy and improving the microstructure morphology through dispersion strengthening, the performance of the ingot as well as after processing and heat treatment will be further improved. The previous dispersion strengthening method was to directly add the dispersion strengthening phase to the casting liquid and disperse the strengthening phase by stirring. Due to the difference in density between the strengthening phase and the casting liquid or the incompatibility of the components, the strengthening phase has low solubility or segregation, which has limitations on the improvement of microstructure size and morphology. Summary of the invention
[0004] The present invention provides a nickel carbide dispersion-strengthened copper-nickel-tin alloy and a preparation method thereof. By effectively and uniformly dispersing the dispersion-strengthened phase in the copper-nickel-tin alloy, the grain size can be refined, the grain morphology can be improved, the intergranular segregation can be reduced, and the mechanical strength and corrosion resistance of the alloy material can be improved.
[0005] In order to solve the above technical problems, one of the purposes of the present invention is to provide a method for preparing a copper-nickel-tin alloy reinforced by nickel carbide dispersion strengthening, comprising the following steps:
[0006] (1) mixing pure nickel powder and graphene and then subjecting them to high-energy ball milling to allow the nickel particles and graphene to combine at the atomic level to obtain a mixed powder;
[0007] (2) pressing the mixed powder into a blank, and then sintering it in an inert gas atmosphere to obtain a nickel-based composite blank containing Ni3C;
[0008] (3) Using a vacuum continuous casting furnace to smelt the alloy, pure copper is first added for refining during smelting;
[0009] (4) After the refining is completed, a nickel-based composite billet containing Ni3C and other raw materials are added according to the composition ratio of the copper-nickel-tin alloy to carry out alloying smelting, and after the smelting is completed, continuous casting is carried out to form billets.
[0010] By adopting the above scheme, the present invention uniformly disperses the dispersion strengthening phase Ni3C in the copper-nickel-tin alloy to control the alloy structure size and morphology. Crystal dislocation is an internal microscopic defect. Dispersed ultrafine particles are used to hinder the movement of dislocations, refine grains, and reduce intercrystalline segregation, thereby improving the mechanical properties of the material at high temperatures, while increasing the number of grain boundaries in the alloy, improving the grain boundary strength, and improving the strength and hardness of the alloy; at the same time, the present invention performs high-energy ball milling on graphene and nickel powder to achieve atomic-level bonding, and then generates Ni3C in situ in the nickel matrix through a sintering process, thereby achieving effective addition of the dispersion strengthening phase Ni3C without introducing new alloy elements, and because nickel and graphene are carbonized, natural nano-scale carbides can be formed due to their characteristics, and are uniformly dispersed in the nickel matrix, which can avoid the problem of losing the strengthening effect on the alloy material due to low solubility or segregation when the dispersion strengthening phase is added alone. The performance of the copper-nickel-tin alloy can be effectively improved.
[0011] As a preferred embodiment, in step (1), the mass ratio of the pure nickel powder to graphene is greater than 15:1.
[0012] By adopting the above scheme, the nickel powder raw material in the nickel-based composite blank is excessive. The purpose is that the excessive nickel powder can reduce the agglomeration of graphene during high-energy ball milling. Secondly, the excessive nickel powder is convenient for sintering and molding the pre-combined alloy mixed powder in the subsequent sintering process, and the excessive nickel powder is convenient for obtaining smaller Ni3C particles in the nickel-based composite blank.
[0013] As a preferred embodiment, in step (1), the particle size of the pure nickel powder is 0.5-10 μm.
[0014] As a preferred solution, the copper-nickel-tin alloy includes 1wt%-20wt% nickel, 1wt%-15wt% tin, 0.001wt%-2wt% Ni3C, and the remainder is copper and inevitable impurities.
[0015] As a preferred embodiment, in step (4), other raw materials include pure nickel and pure tin.
[0016] As a preferred embodiment, in step (1), the high-energy ball mill is a planetary ball mill or a vibration ball mill, the ball-to-material mass ratio of the planetary ball mill is (5-25):1, the rotation speed is 150r / min-350r / min, and the ball milling time is 6h-15h; the ball-to-material mass ratio of the vibration ball mill is (5-25):1, the vibration frequency is 20Hz-60 Hz, and the ball milling time is 6h-15h.
[0017] As a preferred embodiment, in step (1), the high-energy ball milling is carried out in an inert gas atmosphere, and the ball milling process control agent is anhydrous ethanol or stearic acid.
[0018] As a preferred embodiment, 1-3 mL of anhydrous ethanol or 1-4 g of stearic acid is added to every 100 g of the mixed material.
[0019] As a preferred embodiment, in step (2), the sintering temperature is 1100° C.-1450° C., and the sintering time is 0.5-3 h.
[0020] As a preferred solution, the graphene is single-layer graphene.
[0021] By adopting the above scheme, since multilayer graphene will increase the possibility of graphene agglomeration during the preparation process, the generated Ni3C particle size is relatively large, and the generation rate of Ni3C in the nickel-based composite blank will be reduced. The thickness of the single-layer graphene sheet used in the present application is only about 0.35nm. Even if graphene agglomerates during ball milling, since the solid solubility of carbon in nickel is low and nickel and graphene can only undergo carbonization behavior of several atomic layers in thickness, the size of the nickel carbide particles obtained by the reaction after sintering is all nanometer-level.
[0022] As a preferred embodiment, in step (3), the refining temperature is 1200°C-1450°C, and the refining time is 20min-60min.
[0023] As a preferred embodiment, in step (4), the refining temperature is 1200°C-1450°C, and the refining time is 20min-60min.
[0024] As a preferred solution, in step (4), the Ni3C in the copper-nickel-tin alloy is provided by a nickel-based composite billet, and the required addition amount of the nickel-based composite billet is calculated based on the Ni3C mass fraction of 40wt%-60wt% contained in the nickel-based composite billet.
[0025] In order to solve the above technical problems, the second purpose of the present invention is to provide a copper-nickel-tin alloy strengthened by nickel carbide dispersion strengthening.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention uniformly disperses the dispersion reinforcement phase Ni3C in the copper-nickel-tin alloy to regulate the alloy structure size and morphology, thereby improving the mechanical properties of the material at high temperatures, while increasing the number of grain boundaries in the alloy, improving the grain boundary strength, and improving the strength and hardness of the alloy.
[0028] 2. The present invention performs high-energy ball milling on graphene and nickel powder to achieve atomic-level bonding, and then generates Ni3C in situ in the nickel matrix through a sintering process, thereby achieving effective addition of the dispersion-strengthened phase Ni3C without introducing new alloy elements. Moreover, when nickel and graphene are carbonized, natural nano-scale carbides can be formed due to their characteristics, and are evenly dispersed in the nickel matrix. This can avoid the problem of losing the strengthening effect on the alloy material due to low solubility or segregation when the dispersion-strengthened phase is added alone, thereby effectively improving the performance of the copper-nickel-tin alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 :Atomic force microscope morphology image of single-layer graphene;
[0030] Figure 2 : This is the scanning electron microscope morphology image of the mixed powder obtained in step (1) of the method for preparing a copper-nickel-tin alloy enhanced by nickel carbide dispersion strengthening in Example 1 of the present application. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] A copper-nickel-tin alloy strengthened by nickel carbide dispersion strengthening, wherein the copper-nickel-tin alloy is a Cu-15Ni-8Sn alloy composition, comprising 15wt% nickel, 8wt% tin, Ni3C and the remainder copper, and a preparation method thereof comprises the following steps:
[0034] (1) Pure nickel powder with a particle size of 5 μm and single-layer graphene are mixed for high-energy planetary ball milling. The thickness of the single-layer graphene is about 0.35 nm. The mass ratio of pure nickel powder to single-layer graphene is 50:1. Anhydrous ethanol is selected as a control agent for the ball milling process. The content of anhydrous ethanol added per 100 g of the mixed material is 2 mL. The mass ratio of the ball to the material is 10:1. The rotation speed is 180 r / min. After each 15 min of ball milling, there is a pause of 10 min. The ball milling is accumulated for 10 h to obtain a mixed powder.
[0035] like Figure 1-2 , Figure 1 is the morphology of single-layer graphene before ball milling. Figure 2 This is the morphology of the mixed powder after ball milling. It can be seen that the nickel particles are embedded in the graphene sheets, and some nickel particles are flattened and deformed to form a parallel fit with the graphene, so that the metal nickel and graphene are combined at the atomic level;
[0036] (2) The mixed powder is pressed into a cylindrical blank with a diameter of 30 mm in a mold, and then sintered in an atmosphere furnace in an argon atmosphere at a sintering temperature of 1250° C. and a holding time of 2 h, so that the atomic-level metal nickel and graphene react to generate Ni3C, thereby obtaining a nickel-based composite blank containing nano-sized Ni3C. Since the agglomeration and reaction efficiency cannot reach 100%, the Ni3C content in the nickel-based composite blank obtained after sintering cannot be directly calculated according to the mass fraction before ball milling. It is estimated by measurement that 50wt% of the graphene reacts with nickel to generate Ni3C in the nickel-based composite blank;
[0037] (3) A vacuum continuous casting furnace is used for alloy smelting. During smelting, pure copper is first refined at a refining temperature of 1300°C for 40 min. After refining, a nickel-based composite billet containing Ni3C, pure nickel and pure tin are added according to the alloy component ratio. The dispersion-strengthened phase Ni3C content is added at a mass fraction of 0.05wt%, and alloying smelting is performed at a smelting temperature of 1300°C for 30 min. After smelting, continuous casting is performed to form billets.
[0038] Among them, step (2) estimates that 50wt% of graphene reacts with nickel in the nickel-based composite blank to form Ni3C, and calculates the required addition amount of dispersion-strengthened phase Ni3C accounting for 0.05wt% of the product mass fraction according to the estimated proportion of Ni3C in the nickel-based composite blank.
[0039] Example 2
[0040] A copper-nickel-tin alloy enhanced by nickel carbide dispersion strengthening, wherein the steps of the preparation method thereof and the reagents and process parameters used in the steps are the same as those in Example 1, except that in step (3), a vacuum continuous casting furnace is used for alloy smelting, and pure copper is first refined during smelting at a refining temperature of 1300° C. for 40 min. After the refining is completed, a nickel-based composite billet containing Ni3C, pure nickel and pure tin are added according to the alloy component ratio, and the dispersion strengthening phase Ni3C content is added at a mass fraction of 0.03wt%, and alloying smelting is carried out at a smelting temperature of 1300° C. for 30 min. After the smelting is completed, continuous casting is carried out to form billets.
[0041] Example 3
[0042] A copper-nickel-tin alloy enhanced by nickel carbide dispersion strengthening, wherein the steps of the preparation method thereof and the reagents and process parameters used in the steps are the same as those in Example 1, except that in step (3), a vacuum continuous casting furnace is used for alloy smelting, and pure copper is first refined during smelting at a refining temperature of 1300° C. for 40 min. After the refining is completed, a nickel-based composite billet containing Ni3C, pure nickel and pure tin are added according to the alloy component ratio, and the dispersion strengthening phase Ni3C content is added at a mass fraction of 0.08wt%, and alloying smelting is carried out at a smelting temperature of 1300° C. for 30 min. After the smelting is completed, continuous casting is carried out to form billets.
[0043] Comparative Example 1
[0044] A copper-nickel-tin alloy strengthened by nickel carbide dispersion strengthening is a Cu-15Ni-8Sn alloy composition, including 15wt% nickel, 8wt% tin and the balance copper, and its preparation method comprises the following steps:
[0045] A vacuum continuous casting furnace is used for alloy smelting. During smelting, pure copper is first refined at a temperature of 1300°C for 40 minutes. After refining, pure nickel and pure tin are added according to the alloy component ratio for alloy smelting at a temperature of 1300°C for 30 minutes. After smelting, continuous casting is performed into billets.
[0046] Performance testing
[0047] 1. The tensile strength and yield strength of the copper-nickel-tin alloy prepared in the embodiment and the comparative example were tested according to the room temperature tensile test method standard GB / T 34505-2017. The test results are shown in Table 1 below.
[0048] 2. The copper-nickel-tin alloy prepared in the embodiment and the comparative example was subjected to salt spray test according to GB / T 10125 artificial atmosphere salt spray-neutral salt spray test standard. The test results are shown in Table 1 below.
[0049] 3. The hardness of the copper-nickel-tin alloy prepared in the embodiment and the comparative example was tested using a Vickers hardness tester. The test results are shown in Table 1 below.
[0050] Table 1 - Performance test results of copper-nickel-tin alloy prepared by embodiments of the present invention and comparative examples
[0051] Test items Tensile strength(MPa) Yield strength (MPa) Hardness(Hv) Salt spray test Example 1 392.76 378.52 223.7 No surface corrosion Example 2 381.47 367.56 215.4 No surface corrosion Example 3 415.23 395.81 231.9 No surface corrosion Comparative Example 1 363.98 357.29 191.3 -
[0052] As shown in Table 1, the present invention controls the size and morphology of the alloy structure by adding uniformly dispersed Ni3C in the copper-nickel-tin alloy. Crystal dislocation is an internal microscopic defect. Dispersed ultrafine particles are used to hinder the movement of dislocations, refine grains, and reduce intergranular segregation, thereby improving the mechanical properties of the material at high temperatures, while increasing the number of grain boundaries in the alloy, improving the grain boundary strength, and improving the strength and hardness of the alloy. In Examples 1-3, as the amount of dispersion-enhanced Ni3C added increases, the tensile strength, hardness, and yield strength of the alloy material gradually increase. Compared with the copper-nickel-tin alloy in Comparative Example 1 in which the dispersion-enhanced Ni3C is not dispersed, the tensile strength and hardness of the alloy material in Examples 1-2 are significantly higher than those of the alloy material in Comparative Example 1, and the tensile strength, hardness, and yield strength of the alloy material in Example 3 are significantly higher than those of the alloy material in Comparative Example 1.
[0053] At the same time, the present invention performs high-energy ball milling on graphene and nickel powder to achieve atomic-level bonding, and then generates Ni3C in situ in the nickel matrix through a sintering process, thereby achieving effective addition of the dispersion-strengthened phase Ni3C without introducing new alloy elements. Moreover, when nickel and graphene are carbonized, natural nano-scale carbides can be formed due to their characteristics, and are evenly dispersed in the nickel matrix, thereby avoiding the problem of losing the strengthening effect on the alloy material due to low solubility or segregation when the dispersion-strengthened phase is added alone, and effectively improving the performance of the copper-nickel-tin alloy.
[0054] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a copper-nickel-tin alloy reinforced by nickel carbide dispersion strengthening, characterized in that: The following steps are involved: (1) mixing pure nickel powder and graphene and then subjecting them to high-energy ball milling to allow the nickel particles and graphene to combine at the atomic level to obtain a mixed powder; (2) pressing the mixed powder into a blank, and then sintering it in an inert gas atmosphere to obtain a nickel-based composite blank containing Ni3C; (3) Using a vacuum continuous casting furnace to smelt the alloy, pure copper is first added for refining during smelting; (4) After the refining is completed, a nickel-based composite billet containing Ni3C and other raw materials are added according to the composition ratio of the copper-nickel-tin alloy to carry out alloying smelting, and after the smelting is completed, continuous casting is carried out to form billets.
2. The method for preparing a nickel carbide dispersion strengthened copper-nickel-tin alloy as claimed in claim 1, characterized in that: In step (1), the mass ratio of the pure nickel powder to graphene is greater than 15:
1.
3. The method for preparing a copper-nickel-tin alloy reinforced by nickel carbide dispersion strengthening as claimed in claim 1, characterized in that: The copper-nickel-tin alloy comprises 1wt%-20wt% nickel, 1wt%-15wt% tin, 0.001wt%-2wt% Ni3C, and the remainder is copper and inevitable impurities.
4. The method for preparing a nickel carbide dispersion strengthened copper-nickel-tin alloy as claimed in claim 1, characterized in that: In step (1), the high-energy ball mill is a planetary ball mill or a vibration ball mill. The ball-to-material mass ratio of the planetary ball mill is (5-25):1, the rotation speed is 150r / min-350r / min, and the ball milling time is 6h-15h; the ball-to-material mass ratio of the vibration ball mill is (5-25):1, the vibration frequency is 20Hz-60 Hz, and the ball milling time is 6h-15h.
5. The method for preparing a nickel carbide dispersion strengthened copper-nickel-tin alloy as claimed in claim 1, characterized in that: In step (1), the high-energy ball milling is carried out in an inert gas atmosphere, and the ball milling process control agent is anhydrous ethanol or stearic acid. 1-3 mL of anhydrous ethanol or 1-4 g of stearic acid is added to every 100 g of the mixed material.
6. The method for preparing a copper-nickel-tin alloy reinforced by nickel carbide dispersion strengthening as claimed in claim 1, characterized in that: In step (2), the sintering temperature is 1100° C.-1450° C., and the sintering time is 0.5-3 h.
7. The method for preparing a nickel carbide dispersion strengthened copper-nickel-tin alloy as claimed in claim 1, characterized in that: The graphene is single-layer graphene.
8. The method for preparing a nickel carbide dispersion strengthened copper-nickel-tin alloy as claimed in claim 1, characterized in that: In step (3), the refining temperature is 1200°C-1450°C, and the refining time is 20min-60min; In step (4), the refining temperature is 1200°C-1450°C, and the refining time is 20min-60min.
9. The method for preparing a nickel carbide dispersion strengthened copper-nickel-tin alloy as claimed in claim 1, characterized in that: In step (4), the Ni3C in the copper-nickel-tin alloy is provided by a nickel-based composite billet, and the required addition amount of the nickel-based composite billet is calculated based on the fact that the nickel-based composite billet itself contains 40wt%-60wt% Ni3C.
10. A nickel carbide dispersion strengthened copper-nickel-tin alloy prepared by the method for preparing a nickel carbide dispersion strengthened copper-nickel-tin alloy as claimed in any one of claims 1 to 9.